FEATURES OF TOURIST INTEGRATION ENTERPRISES - Shatska, Zorina; Melnyk, Alona; Sigya, George (Socio-Cultural Management Journal, 2020)
Introduction. The tourism sector is the most globalized sector of the world economy, as it is constantly expanding its activities in the countries of the world, opening up new opportunities for development. Globalization conditions of business development require enterprises in the sphere of tourism to work closely together and to consolidate their activity, to find new ways of cooperation. This is very difficult to achieve in the context of isolated activity, when the enterprise is a closed system, so in the field of tourism to become effective enterprises get open systems, which are forced to create complex business structures, which include enterprises from different fields of activity and different countries of affiliation, which ensures their further development. Purpose and methods. The purpose of the study is to analyze and systematize the forms and directions of integration of tourism and other companies operating in the tourism market in the context of the systematic integration of tourism enterprises in the global space. The research uses such general scientific methods as monographic, system analysis, synthesis, and generalization. Results. The article found that the integration of tourism enterprises can be carried out in three directions: integration in the formation of a tourism product; integration in the promotion and sale of the tourism product; integration of financial support for the processes of formation, promotion and sale of the tourism product. In each of the areas of integration, tourist enterprises can choose different forms of organization of their activities, which forms a system of integration of tourist enterprises. Conclusions. The scientific novelty of the obtained results is the formation of a system of integration of tourist enterprises, which, unlike the existing ones, allows the tourism industry enterprises, depending on the stage of work with the tourism product (formation; promotion and sale; financial support) to choose the directions and forms of cooperation through specialization, cooperation, concentration. The practical significance of the obtained results lies in the possibility of their application in the practical activity of domestic enterprises of the tourism industry to increase the efficiency of their activity, increase competitiveness and as one of the possible strategic directions for further development.